A polyethylene glycol monomethyl ether polylactic acid copolymer, its preparation method and its application

By scientifically selecting the feed ratio of polyethylene glycol derivatives and lactide and using modified silica gel column chromatography, the problems of tin residue and uneven molecular weight distribution in polyethylene glycol polylactic acid copolymers were solved, and a highly efficient and safe polyethylene glycol derivative polylactic acid copolymer suitable for medical carriers was prepared.

CN116102721BActive Publication Date: 2026-11-06MEIYAN SPACE (HEBEI) BIOTECHNOLOGY CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211405926.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-11-10
Filing Date
2022-11-10
Publication Date
2026-11-06
Estimated Expiration
2042-11-10

AI Technical Summary

Technical Problem

Existing polyethylene glycol polylactic acid copolymers have the problem of residual tin catalysts during the preparation process, and the molecular weight distribution is uneven, which affects the biodegradation cycle and biocompatibility, making it difficult to meet the requirements of medical carriers.

Method used

By scientifically selecting the feed ratio of polyethylene glycol derivatives and lactide, and through a purification method combining modified silica gel column chromatography and organic solvent extraction, a polyethylene glycol derivative polylactic acid copolymer with uniform molecular weight distribution and low tin residue was prepared.

Benefits of technology

It achieves effective removal of tin residue, improves the hydrophilicity and biocompatibility of copolymers, extends the degradation cycle, is suitable for large-scale industrial production, and meets the requirements of medical carriers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003937138190000111
    Figure BDA0003937138190000111
  • Figure BDA0003937138190000112
    Figure BDA0003937138190000112
Patent Text Reader

Abstract

This invention provides a polyethylene glycol monomethyl ether polylactic acid copolymer, its preparation method, and its applications. The method of this invention allows for the adjustment of the molecular weight and properties of the final product by controlling the feed ratio of polyethylene glycol derivatives to lactide. By controlling the moisture content of the starting materials, the product prepared by this invention has a more uniform molecular weight distribution. This invention also develops a method for removing tin using high-purity mercapto-modified silica gel adsorption. Compared to traditional tin removal methods, this method is simpler to operate, saves costs, and, in particular, achieves the technical effect of undetectable heavy metal residues, making it especially suitable for large-scale industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of pharmaceutical technology, specifically to a biodegradable polyethylene glycol monomethyl ether polylactic acid copolymer, its preparation method, and its applications. Background Technology

[0002] Polymer medical carriers include natural polymers (such as polysaccharides and proteins) and synthetic polymers (such as homopolymers and copolymers). The limited structure and composition of homopolymers result in limited performance, thus restricting their application in medical carriers. Copolymers prepared by copolymerization modification are widely used as medical carriers. Polyethylene glycol (PEG) has excellent hydrophilicity and biocompatibility, making it the most widely used hydrophilic block copolymer. Furthermore, it avoids recognition and capture by the reticuloendothelial system (RES) and organs such as the liver, spleen, and kidneys in vivo, resulting in a longer blood circulation time. PEG-polylactic acid polymeric block copolymers prepared by polymerizing polylactic acid and PEG contain both hydrophilic and hydrophobic segments, are free of peptide chains, are non-immunogenic, biodegradable, and their degradation products are readily excreted from the body without accumulation. Therefore, they have been developed as carriers for hydrophobic drugs. For example, Genexol-PM, developed and marketed by Samyang, is a polylactic acid polyethylene glycol micelle of paclitaxel. It was approved for marketing in South Korea in 2007 for the treatment of breast cancer and non-small cell lung cancer.

[0003] The preparation of polyethylene glycol-polylactic acid copolymers requires polyethylene glycol or its derivatives as initiators and the ring-opening polymerization of lactide using tin-based catalysts. However, tin-based catalysts are toxic, and stannous ions are easily oxidized. Therefore, it is necessary to detect and monitor the tin content in the polyethylene glycol-polylactic acid copolymer to ensure its safe and effective use.

[0004] CN105315444A discloses a method for purifying polyethylene glycol monomethyl ether polylactic acid (PEG-PLA) using a strongly acidic cation exchange resin chromatography column. This method employs a 0.22 μm microporous membrane for filtration, but the operation is extremely cumbersome and unsuitable for large-scale industrial production, and it struggles to address the issue of residual tin in the copolymer. While organic solvent extraction can remove residual tin from the copolymer, it affects production efficiency and yield. Furthermore, the molecular weight distribution of PEG-PLA copolymers is directly related to their biodegradation cycle and filling effect, influencing batch-to-batch differences and dispersion stability. Improving the hydrophilicity and biocompatibility of the copolymer is crucial for enhancing its filling effect. Therefore, there is a need to develop PEG-derived PLA copolymers with better hydrophilicity and biocompatibility, more uniform molecular weight distribution, longer degradation cycles, and safety and effectiveness, as well as their preparation methods. Summary of the Invention

[0005] To address the shortcomings of existing technologies, this invention provides a method for preparing polyethylene glycol derivative polylactic acid copolymers, which scientifically selects the feeding ratio of polyethylene glycol derivatives and lactide and the purification method to prepare copolymers that meet medical requirements.

[0006] The purpose of this invention is to provide a method for preparing a polyethylene glycol derivative polylactic acid copolymer, comprising the following steps:

[0007] (1) Weigh polyethylene glycol derivative and lactide at a weight ratio of 1-10:1, mix them uniformly under stirring, evacuate and melt the reactants at 80℃-150℃ under inert gas protection, then add 0.1%-1% tin catalyst and complete the polymerization reaction at 80℃-150℃ to obtain polyethylene glycol derivative polylactic acid copolymer, wherein the polyethylene glycol derivative is a terminal polyethylene glycol with one terminal hydroxyl group reacting, and the terminal polyethylene glycol is selected from polyethylene glycol monomethyl ether (PEG). The ester is selected from any one or a combination of mPEG, ethoxy polyethylene glycol, and propoxy polyethylene glycol; the inert gas is selected from any one or a combination of nitrogen, argon, and helium; and the tin catalyst is selected from any one or a combination of stannous octoate, stannous chloride, stannous sulfate, dibutyltin diacetate, dibutyltin dibenzoate, dibutyltin diisocyanate, tri-n-butylmethoxytin, dibutyltin dilaurate, and diethyltin.

[0008] (2) After the reaction is completed, the reaction system is cooled to 20-35℃, and a good solvent is added to the obtained polyethylene glycol derivative polylactic acid copolymer. The mixture is stirred until completely dissolved to obtain a copolymer solution. Tin is then removed by any one or a combination of organic solvent extraction, column chromatography, activated carbon adsorption, modified silica gel column chromatography, and modified silica gel adsorption to obtain a tin removal solution. The good solvent is selected from any one or a combination of tetrahydrofuran, 1,4-dioxane, dichloromethane, chloroform, N,N-dimethylformamide, dimethyl sulfoxide, ethylene glycol diethyl ether, ethylene glycol dimethyl ether, toluene, and p-xylene.

[0009] (3) Filter the detinning solution, concentrate it under reduced pressure until the good solvent evaporates, add the unsuitable solvent of polyethylene glycol derivative polylactic acid copolymer to the concentrate, precipitate the solid, filter, wash the filter cake, and dry to obtain polyethylene glycol derivative polylactic acid copolymer, wherein the unsuitable solvent is selected from any one or a combination of methanol, ethanol, isopropanol, n-propanol, butanol, acetone, butanone, ethyl acetate, diethyl ether, and isopropyl ether.

[0010] The obtained polyethylene glycol derivative polylactic acid copolymer has a molecular weight distribution of 1.01-1.5 and tin residue <10ppm.

[0011] In a preferred embodiment of the present invention, the polylactic acid is selected from any one or a combination of poly-L-lactic acid (PLLA), poly-D-lactic acid (PDLA), and poly-racemic lactic acid (PDLLA).

[0012] In a preferred embodiment of the present invention, the copolymer is composed of PLLA and mPEG, wherein the mPEG is selected from any one or a combination of mPEG-400, mPEG-1000, mPEG-2000, mPEG-4000, mPEG-5000, mPEG-8000, and mPEG-10000.

[0013] In a preferred embodiment of the present invention, the polyethylene glycol derivative and / or lactide are subjected to a dehydration process.

[0014] In a preferred embodiment of the present invention, the water removal method is selected from any one or a combination of azeotropic solvent dehydration and vacuum dehydration, and preferably the azeotropic solvent is selected from any one or a combination of benzene, toluene, xylene, and dioxane.

[0015] In a preferred embodiment of the present invention, the weight ratio of polyethylene glycol derivative to lactide in the reaction system is selected from any one of 1:1, 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1, 5:1, 5.5:1, 6:1, 6.5:1, 7:1, 7.5:1, 8:1, 8.5:1, 9:1, 9.5:1, and 10:1.

[0016] In a preferred embodiment of the present invention, the polymerization reaction is carried out at 100℃-140℃, and more preferably at 110℃-135℃.

[0017] In the preferred embodiment of the present invention, the polymerization reaction is completed in 5-15 hours, preferably in 8-12 hours.

[0018] In a preferred embodiment of the present invention, 0.2%-0.5% tin catalyst is added.

[0019] In a preferred embodiment of the present invention, the modified silica gel used in the modified silica gel column chromatography or modified silica gel adsorption method is mercapto-modified silica gel.

[0020] In a preferred embodiment of the present invention, the modified silica gel used in the modified silica gel column chromatography or modified silica gel adsorption method is high-purity mercapto-modified silica gel.

[0021] In a preferred embodiment of the present invention, the amount of silica gel used in the modified silica gel adsorption method accounts for 0.5%-2% of the mass percentage of the copolymer to be purified, preferably 1%-1.5%.

[0022] In a preferred embodiment of the present invention, the weight-average molecular weight of the copolymer prepared is 2000Da-25000Da, preferably 4000Da-22000Da, and more preferably 10000Da-13000Da.

[0023] In a preferred embodiment of the present invention, the molecular weight distribution of the copolymer is 1.02-1.25.

[0024] In a preferred embodiment of the present invention, the tin residue of the copolymer is any one of <9ppm, <8ppm, <7ppm, <6ppm, <5ppm, <4ppm, <3ppm, <2ppm, or <1ppm.

[0025] In the preferred embodiment of the present invention, the tin residue in the obtained copolymer is undetectable.

[0026] This invention also provides a method for preparing an aqueous solution of the polyethylene glycol derivative polylactic acid copolymer obtained by the above preparation method, the preparation method comprising:

[0027] The purified copolymer was added to water and stirred until completely dissolved. The solution was then transferred to a volumetric flask and diluted to volume with water. The diluted solution was then filtered through a filter membrane, the pore size of which was selected from any one of 1 μm, 0.45 μm, 0.22 μm or a combination thereof.

[0028] In a preferred embodiment of the present invention, the water is selected from any one or a combination of ultrapure water, distilled water, and deionized water.

[0029] The present invention also provides the application of the polyethylene glycol derivative polylactic acid copolymer obtained by the above preparation method in the preparation of a carrier for a hydrophobic drug.

[0030] The present invention also provides an application of the polyethylene glycol derivative polylactic acid copolymer obtained by the above preparation method in the preparation of medical and cosmetic products.

[0031] The present invention also provides the application of the polyethylene glycol derivative polylactic acid copolymer obtained by the above preparation method in the preparation of a biodegradable injection filler.

[0032] In a preferred embodiment of the present invention, the filling site of the filler is selected from any one or a combination of the face, neck, abdomen, chest, buttocks, thigh, calf, upper arm, and lower arm.

[0033] Another object of the present invention is to provide a composition comprising a polyethylene glycol derivative polylactic acid copolymer obtained by the above preparation method.

[0034] In a preferred embodiment of the present invention, the copolymer in the composition has a molecular weight of 7000 Da-1,5000 Da.

[0035] In a preferred embodiment of the present invention, the copolymer in the composition has a molecular weight of 9000 Da-14000 Da.

[0036] In a preferred embodiment of the present invention, the copolymer in the composition has a molecular weight of 1,2000 Da to 1,4000 Da. In a preferred embodiment of the present invention, the composition further comprises any one or a combination of polyols, amino acids, polypeptides, proteins, nucleic acids, vitamins, polysaccharides, and local anesthetics.

[0037] In a preferred embodiment of the present invention, the composition further comprises any one or a combination of polyvinyl alcohol, gelatin, gum arabic, guar gum, chondroitin sulfate, hyaluronic acid, sodium carboxymethyl cellulose, polyvinylpyrrolidone, methylcellulose, hydroxypropyl methylcellulose, starch, pectic acid, heparin, glucose, β-cyclodextrin, chitosan, and sodium alginate.

[0038] In a preferred embodiment of the present invention, the composition is prepared as a liquid injection or a powder injection.

[0039] In a preferred embodiment of the present invention, the liquid injection is selected from any one of hydrogel, suspension, and solution.

[0040] In a preferred embodiment of the present invention, the powder injection is a lyophilized powder injection.

[0041] In a preferred embodiment of the present invention, the lyophilized powder injection comprises any one or a combination of a suspension stabilizer, a surfactant, and a buffer.

[0042] In a preferred embodiment of the present invention, the suspension stabilizer is selected from any one or a combination of sucrose, maltose, lactose, fructose, dextran, mannitol, trehalose, sorbitol, xylitol, maltitol, oligosaccharide alcohols, and polyethylene glycol.

[0043] In a preferred embodiment of the present invention, the surfactant is selected from any one or a combination of stearic acid, sodium dodecyl sulfonate, lecithin, alkyl glucoside, polysorbate, sorbitan fatty acid ester, and poloxamer.

[0044] In a preferred embodiment of the present invention, the buffer is selected from any one or a combination of phosphate-phosphate, citric acid-citrate, EDTA-EDTA salt, citric acid-citrate.

[0045] The present invention also provides a combination of the composition, wherein the composition is used in combination with any one or a combination of other types of injectable fillers, anesthetics, anti-inflammatory agents, anti-allergens, or other similar agents.

[0046] In a preferred embodiment of the present invention, the other types of injectable fillers are selected from any one or a combination of collagen, hyaluronic acid, polymethyl methacrylate, polyacrylamide, silicone, and autologous fat.

[0047] In a preferred embodiment of the present invention, the anesthetic agent is selected from any one or a combination of lidocaine, procaine, tetracaine, bupivacaine, ropivacaine, diclofenac, morphine, hydrocodone, oxycodone, codeine, fentanyl, sodium pentobarbital, sodium phenobarbital, sodium thiopental, chloralose, ethyl carbamate, and chloral hydrate.

[0048] In a preferred embodiment of the present invention, the anti-inflammatory agent is selected from any one or a combination of steroidal anti-inflammatory agents and non-steroidal anti-inflammatory agents.

[0049] In a preferred embodiment of the present invention, the steroidal anti-inflammatory agent is selected from any one or a combination of fluocinolone acetonide, hydrocortisone, and betamethasone.

[0050] In a preferred embodiment of the present invention, the nonsteroidal anti-inflammatory agent is selected from any one or a combination of aspirin, magnesium salicylate, sodium salicylate, magnesium choline salicylate, diflunisal, disalicylate, ibuprofen, indomethacin, flurbiprofen, phenoxyibuprofen, naproxen, nabumetone, piroxicam, phenylbutazone, diclofenac sodium, fenprofen, ketoiprofen, ketorolac, tetraclofenamic acid, sulindac, and tometidine.

[0051] In a preferred embodiment of the present invention, the anti-allergy agent is selected from any one or a combination of diphenhydramine, promethazine, chlorpheniramine, sodium cromoglycate, ketotifen, betahistine, montelukast, zafirust, salbutamol, calcium gluconate, and glucocorticoids.

[0052] To clearly define the scope of protection of this invention, the following terms are defined as follows:

[0053] 1. The “particle size” of the polyethylene glycol monomethyl ether polylactic acid copolymer microparticles described in this invention refers to the particle size (D90) that accounts for 90% of the particle size distribution.

[0054] 2. The particle size distribution of the polyethylene glycol monomethyl ether polylactic acid copolymer microparticles described in this invention was determined using an ultra-high-speed intelligent particle size analyzer under an air pressure of 2.0 barg, a sample feed rate of 35%, and a hopper gap of 1.50 mm.

[0055] 3. The scanning electron microscope (SEM) image of the polyethylene glycol monomethyl ether polylactic acid copolymer microparticles described in this invention was obtained by using a scanning electron microscope (model: Thermo-Prisma E) at 5000x magnification.

[0056] Unless otherwise stated, the present invention uses the following methods to detect the molecular weight of the copolymer, the tin content in the copolymer, and the residual amount of L-lactide.

[0057] 1. The present invention uses gel permeation chromatography (GPC) (Chinese Pharmacopoeia 2020 Edition, Part IV, General Chapter 0514) to detect the molecular weight of copolymers.

[0058] For the test solution, take an appropriate amount of this product, accurately weigh it, dissolve and dilute it with chloroform to prepare a solution containing about 10 mg per ml, filter it through a 0.22 μm organic filter membrane, and collect the filtrate.

[0059] Take appropriate amounts of 5-6 polystyrene reference standards of different molecular weights, accurately weigh them, dissolve and dilute them in chloroform to prepare a solution containing approximately 2 mg of each reference standard per 1 ml, dissolve and mix well.

[0060] Chromatographic conditions: Gel column (Styragel HR 4E THF, 7.8 × 300 mm or equivalent); mobile phase: chloroform; flow rate: 0.7 mL / min; detector: differential refractive index detector; column temperature: 35 °C; injection volume: 10 μL.

[0061] For the assay, accurately measure the test solution and the reference solution, inject them separately into the liquid chromatograph, and record the chromatograms. Use GPC software to calculate the regression equation for the reference solution and the weight-average molecular weight (Mw), number-average molecular weight (Mn), and molecular weight distribution (Mw / Mn) of the test solution.

[0062] 2. The present invention uses inductively coupled plasma mass spectrometry (ICP-MS) (Chinese Pharmacopoeia 2020 edition, Part IV, General Chapter 0412) to detect the tin content of the copolymer.

[0063] For the test solution, accurately weigh approximately 250 mg of the sample and place it in a digestion vessel (55-TMF). Add 8 ml of nitric acid and digest under the prescribed conditions. After digestion, rinse the digestion vessel several times with small amounts of solvent and transfer the rinsed solution to a 25 ml volumetric flask. Dilute to the mark with solvent and mix well. Accurately measure 1 ml of the diluted solution into a 10 ml volumetric flask, add 0.1 ml of internal standard solution, dilute to the mark with solvent, and mix well. This is the test solution. For the blank solution, place 8 ml of nitric acid in a digestion vessel (55-TMF) and digest under the prescribed conditions. After digestion, rinse the digestion vessel several times with small amounts of solvent and transfer the rinsed solution to a 25 ml volumetric flask. Dilute to the mark with solvent and mix well. Accurately measure 1 ml of the diluted solution into a 10 ml volumetric flask, add 0.1 ml of internal standard solution, dilute to the mark with solvent, and mix well. This is the blank solution. For the internal standard solution, accurately measure 0.050 ml of indium standard solution and place it in a 100 ml volumetric flask. Dilute to the mark with solvent and mix well. For the standard curve solution, accurately measure an appropriate amount of tin single-element standard solution and dilute with solvent to prepare a solution containing approximately 600 ng of tin per ml, as a stock solution. Accurately measure 0 ml, 0.1 ml, 0.5 ml, 1.0 ml, 1.5 ml, and 2.0 ml of this solution and place them in separate 10 ml volumetric flasks. Accurately add 0.1 ml of internal standard solution, dilute to the mark with 2% nitric acid solution, and mix well. These are used as Linear 1 to Linear 6, respectively. For the assay, inject the standard curve solution into an inductively coupled plasma mass spectrometer and record the mass spectrum. Plot the standard curve with the ratio of the analytical peak response value of the analyte to the reference peak response value of the internal standard element as the ordinate and the concentration as the abscissa. Calculate the regression equation; the correlation coefficient (r) should not be less than 0.99. Take the test solution and blank solution, inject them into the inductively coupled plasma mass spectrometer, record the mass spectra, and calculate the content of the analyte element using the standard curve method with blank correction.

[0064] 3. In this invention, gas chromatography (Chinese Pharmacopoeia 2020 Edition, Part IV, General Chapter 0521) is used to detect the residual amount of L-lactide in the copolymer.

[0065] For the test solution, take an appropriate amount of this product, accurately weigh it, dissolve it in dichloromethane, and quantitatively dilute it to prepare a solution containing approximately 10 mg per ml.

[0066] For the reference solution, accurately weigh an appropriate amount of L-lactide, dissolve it in dichloromethane, and quantitatively dilute it to prepare a solution containing 0.2 mg per ml.

[0067] Chromatographic conditions: Column (Agilent HP-5, 30m × 0.32mm, 0.25μm or equivalent); initial temperature 80℃, ramped to 170℃ at a rate of 10℃ / min, held for 1 minute; injection port temperature 160℃; detector: flame ionization detector (FID) at 250℃; carrier gas: nitrogen, flow rate 2.5ml / min, split ratio 10:1; injection volume 1μl.

[0068] For the assay, accurately measure the test solution and the reference solution, inject them separately into the gas chromatograph, and record the chromatograms.

[0069] Unless otherwise stated, when this invention relates to percentages between liquids, the percentage is volume / volume percentage; when this invention relates to percentages between liquids and solids, the percentage is volume / weight percentage; when this invention relates to percentages between solids and liquids, the percentage is weight / volume percentage; the remainder is weight / weight percentage.

[0070] Compared with the prior art, the present invention has the following beneficial effects:

[0071] 1. This invention has four main advantages: First, it uses mercapto-modified silica gel to remove residual tin catalyst from intermediate reaction products, reducing tin residue to undetectable levels to ensure safe use. Second, it employs a method of directly adsorbing tin from the solution using modified silica gel, which is simpler to operate, reduces energy consumption and production costs compared to column chromatography, and is particularly suitable for large-scale industrial production, possessing significant industrial value. Third, it removes water from the copolymer preparation raw materials, improving reaction efficiency and yielding copolymers with a more concentrated molecular weight distribution by reducing moisture in the reaction system. Fourth, it scientifically selects the first and second solvents to improve the purity and quality of the copolymer, avoiding the safety hazards of using low-boiling-point, highly toxic diethyl ether solvent, and improving purification efficiency and yield.

[0072] 2. This invention studies the effects of different feed ratios of polyethylene glycol monomethyl ether and lactide in copolymer preparation raw materials on the molecular weight of the final product and the properties of the formulation after preparation with a suitable solvent, so as to obtain drug carriers or medical aesthetic products that meet different needs.

[0073] 3. The polyethylene glycol monomethyl ether polylactic acid copolymer obtained by the preparation method of the present invention has significantly improved hydrophilicity and biocompatibility, significantly improved the cell adhesion ability of the copolymer, significantly prolonged the degradation cycle of the copolymer, and has the advantages of good stability, facilitating the stimulation and acceleration of collagen growth at the injection site, and being safer and more effective. Detailed Implementation

[0074] To make the objectives, technical solutions, and advantages of this invention clearer, the embodiments of this invention will be described in detail below. It should be noted that, unless otherwise specified, the embodiments of this invention and the features within them can be arbitrarily combined with each other.

[0075] The high-purity mercapto-modified silica gel used in the embodiments of this invention was purchased from Wansonghong (Guangzhou) Trading Co., Ltd.

[0076] Example 1: Preparation of mPEG-PLLA of the present invention

[0077] 40g of L-lactide and 160g of polyethylene glycol monomethyl ether with a molecular weight of 5000 were added to a three-necked flask. Under stirring at 200rpm, nitrogen or argon gas was introduced into the reaction system for 30min, and then the oil bath temperature was raised to 120℃ to melt the reaction. 0.6g of stannous octoate was added, and the reaction was carried out at 120℃ for 10h. After the reaction was completed, the reaction system was cooled to room temperature, and 200ml of dichloromethane was added to dissolve the reaction product. 1g of high-purity mercapto-modified silica gel was added to the product solution, and the mixture was stirred for 2h. The mixture was filtered through a 0.45μm filter membrane, and the filtrate was collected. After concentration under reduced pressure to remove most of the solvent, 3000ml of isopropyl ether was slowly added to the concentrate. After the addition was completed, the mixture was stirred for 0.5h, and a solid precipitated. The solid was filtered through filter paper, and the filter cake was collected. After rinsing with isopropyl ether, the solid was dried under vacuum at 40-60℃ to obtain 168g of mPEG-PLLA copolymer.

[0078] Using the method of this invention, the molecular weight of the prepared mPEG-PLLA copolymer was determined to be Mw 15026 Da, Mn 10889 Da, and Mw / Mn = 1.38. Tin residue was 8 ppm. L-lactide residue was 0.33%.

[0079] Example 2: Preparation of mPEG-PLLA of the present invention

[0080] 40g of L-lactide and 160g of polyethylene glycol monomethyl ether with a molecular weight of 5000 were added to a three-necked flask. Under stirring at 200rpm, nitrogen or argon gas was introduced into the reaction system for 30min, and then the oil bath temperature was raised to 120℃ to melt. 0.6g of stannous octoate was added, and the reaction was kept at 120℃ for 10h. After the reaction was completed, the reaction system was cooled to room temperature, and 200ml of dichloromethane was added to dissolve the reaction product. 2g of high-purity mercapto-modified silica gel was added to the solution of the reaction product, and the mixture was stirred for 2h. The mixture was filtered through a 0.45μm filter membrane, the filtrate was collected, and most of the solvent was removed by vacuum concentration. Then, 3000ml of isopropyl ether was slowly added to the concentrate. After the addition was completed, the mixture was stirred for 0.5h, and a solid precipitated. The solid was filtered through filter paper, the filter cake was collected, washed with isopropyl ether, and then dried under vacuum at 30-50℃ to obtain 173g of mPEG-PLLA copolymer.

[0081] Using the method of this invention, the molecular weight of the prepared mPEG-PLLA copolymer was determined to be Mw 14241 Da, Mn 10395 Da, and Mw / Mn = 1.37. Tin residue was 3 ppm. L-lactide residue was 0.28%.

[0082] Example 3: Preparation of mPEG-PLLA of the present invention

[0083] 40g of L-lactide and 160g of polyethylene glycol monomethyl ether with a molecular weight of 5000 were added to a three-necked flask. Under stirring at 200rpm, nitrogen or argon gas was introduced into the reaction system for 30min, and then the oil bath temperature was raised to 120℃ to melt. 0.6g of stannous octoate was added, and the reaction was kept at 120℃ for 10h. After the reaction was completed, the reaction system was cooled to room temperature, and 200ml of dichloromethane was added to dissolve the reaction product. 3g of high-purity mercapto-modified silica gel was added to the solution of the reaction product, and the mixture was stirred for 2h. The mixture was filtered through a 0.45μm filter membrane, the filtrate was collected, and most of the solvent was removed by vacuum concentration. Then, 3000ml of isopropyl ether was slowly added to the concentrate. After the addition was completed, the mixture was stirred for 0.5h, and a solid precipitated. The solid was filtered through filter paper, the filter cake was collected, washed with isopropyl ether, and then dried under vacuum at 30-50℃ to obtain 170g of mPEG-PLLA copolymer.

[0084] Using the method of this invention, the molecular weight of the prepared mPEG-PLLA copolymer was determined to be Mw 12638 Da, Mn 9503 Da, and Mw / Mn = 1.33. No tin residue was detected. The residual L-lactide content was 0.26%.

[0085] Example 4: Preparation of mPEG-PLLA of the present invention

[0086] 40g of L-lactide and 160g of polyethylene glycol monomethyl ether with a molecular weight of 5000 were added to a three-necked flask. Under stirring at 200rpm, nitrogen or argon gas was introduced into the reaction system for 30min, and then the oil bath temperature was raised to 120℃ to melt the reaction. 0.6g of stannous octoate was added, and the reaction was carried out at 120℃ for 10h. After the reaction was completed, the reaction system was cooled to room temperature, and 200ml of dichloromethane was added to dissolve the reaction product. 3g of high-purity mercapto-modified silica gel was added to the product solution, and the mixture was stirred for 2h. The mixture was filtered through a 0.45μm filter membrane, and the filtrate was collected. After concentration under reduced pressure to remove most of the solvent, 5000ml of isopropyl ether was slowly added to the concentrate. After the addition was completed, the mixture was stirred for 0.5h, and a solid precipitated. The solid was filtered through filter paper, and the filter cake was collected. After rinsing with isopropyl ether, the solid was dried under vacuum at 30-50℃ to obtain 182g of mPEG-PLLA copolymer.

[0087] Using the method of this invention, the molecular weight of the prepared mPEG-PLLA copolymer was determined to be Mw 12858 Da, Mn 9525 Da, and Mw / Mn = 1.35. No tin residue was detected. The residual L-lactide content was 0.31%.

[0088] Example 5: Preparation of mPEG-PLLA of the present invention

[0089] 40g of L-lactide and 160g of polyethylene glycol monomethyl ether with a molecular weight of 5000 were added to a three-necked flask. Under stirring at 200rpm, nitrogen or argon gas was introduced into the reaction system for 30min, and then the oil bath temperature was raised to 120℃ to melt the reaction. 0.6g of stannous octoate was added, and the reaction was carried out at 120℃ for 10h. After the reaction was completed, the reaction system was cooled to room temperature, and 200ml of dichloromethane was added to dissolve the reaction product. 10g of activated carbon was added to the solution of the reaction product, and the mixture was stirred for 10h. The mixture was filtered through a 0.22μm filter membrane, and the filtrate was collected. After concentration under reduced pressure to remove most of the solvent, 5000ml of isopropyl ether was slowly added to the concentrate. After the addition was completed, the mixture was stirred for 0.5h, and a solid precipitated. The solid was filtered through filter paper, and the filter cake was collected. After rinsing with isopropyl ether, the solid was dried under vacuum at 30-50℃ to obtain 180g of mPEG-PLLA copolymer.

[0090] Using the method of this invention, the molecular weight of the prepared mPEG-PLLA copolymer was determined to be Mw 14571 Da, Mn 10874 Da, and Mw / Mn = 1.34. The tin residue was 80.5 ppm. The L-lactide residue was 0.29%.

[0091] Example 6: Preparation of mPEG-PLLA of the present invention

[0092] 40g of L-lactide and 160g of polyethylene glycol monomethyl ether with a molecular weight of 5000 were added to a three-necked flask. Under stirring at 200rpm, nitrogen or argon gas was introduced into the reaction system for 30min, and then the oil bath temperature was raised to 120℃ to melt the reaction. 0.6g of stannous octoate was added, and the reaction was carried out at 120℃ for 10h. After the reaction was completed, the reaction system was cooled to room temperature, and 200ml of dichloromethane was added to dissolve the reaction product. 10g of activated carbon was added to the solution of the reaction product, and the mixture was stirred for 10h. The mixture was filtered through a 0.22μm filter membrane, and the filtrate was collected. After concentration under reduced pressure to remove most of the solvent, 5000ml of isopropyl ether was slowly added to the concentrate. After the addition was completed, the mixture was stirred for 0.5h, and a solid precipitated. The solid was filtered through filter paper, and the filter cake was collected. After rinsing with isopropyl ether, the solid was dried under vacuum at 30-50℃ to obtain 184g of mPEG-PLLA copolymer.

[0093] Using the method of this invention, the molecular weight of the prepared mPEG-PLLA copolymer was determined to be Mw 15577 Da, Mn 11048 Da, and Mw / Mn = 1.41. The tin residue was 74.40 ppm. The L-lactide residue was 0.27%.

[0094] Example 7: Preparation of mPEG-PLLA of the present invention

[0095] 40g of L-lactide and 160g of polyethylene glycol monomethyl ether with a molecular weight of 5000 were added to a three-necked flask. Under stirring at 200rpm, nitrogen or argon gas was introduced into the reaction system for 30min, and then the oil bath temperature was raised to 120℃ to melt the reaction. 0.6g of stannous octoate was added, and the reaction was kept at 120℃ for 10h. After the reaction was completed, the reaction system was cooled to room temperature, and 200ml of dichloromethane was added to dissolve the reaction product. The product was purified by column chromatography using high-purity mercapto-modified silica gel, with a mixture of dichloromethane and ethyl acetate as the eluent. The chromatographic solution was distilled to remove most of the solvent, and 5000ml of isopropyl ether was slowly added dropwise. After the addition was completed, the mixture was stirred for 0.5h to precipitate a solid. The solid was filtered, and the filter cake was washed with isopropyl ether. The filter cake was dried under vacuum at 30-50℃ to obtain 171g of mPEG-PLLA copolymer.

[0096] Using the method of this invention, the molecular weight of the prepared mPEG-PLLA copolymer was determined to be Mw 12551 Da, Mn 9030 Da, and Mw / Mn = 1.39. No tin residue was detected. L-lactide residue was 0.10%.

[0097] Example 8: Preparation of mPEG-PLLA of the present invention

[0098] Take 400g of polyethylene glycol monomethyl ether sample with a molecular weight of 5000 and add it to a round-bottom beaker. Add 800ml of toluene, connect the flask to an oil-water separator, and place it in a 120℃ oil bath for azeotropic dehydration for 5 hours. After azeotroping, rotary evaporate the sample to remove residual toluene and seal it for storage. The water content of the sample before dehydration was 1.13%, and the water content after dehydration was 0.0103%. Add 40g of [unspecified substance] to a three-necked flask. L-lactide and 160g of polyethylene glycol monomethyl ether were stirred at 200rpm, and nitrogen or argon gas was introduced into the reaction system for 30min. The system was then heated to 120℃ in an oil bath to melt the mixture. 0.6g of stannous octoate was added, and the reaction was carried out at 120℃ for 10h. After the reaction was completed, the reaction system was cooled to room temperature, and 200ml of dichloromethane was added to dissolve the reaction product. 3g of high-purity mercapto-modified silica gel was added to the solution of the reaction product, and the mixture was stirred for 2h. The mixture was filtered through a 0.45μm filter membrane, and the filtrate was collected. After concentration under reduced pressure to remove most of the solvent, 5000ml of isopropyl ether was slowly added to the concentrate. After the addition was complete, the mixture was stirred for 0.5h, and a solid precipitated. The solid was filtered through filter paper, and the filter cake was collected. After rinsing with isopropyl ether, the solid was dried under vacuum at 30-50℃ to obtain 185g of mPEG-PLLA copolymer.

[0099] Using the method of this invention, the molecular weight of the prepared mPEG-PLLA copolymer was determined to be Mw 14425 Da, Mn 12766 Da, and Mw / Mn = 1.13. No tin residue was detected. The residual L-lactide content was 0.28%.

[0100] Example 9: Preparation of mPEG-PLLA of the present invention

[0101] Take 400g of lactide sample and add it to a round-bottom beaker. Add 800ml of toluene, connect the flask to an oil-water separator, and place it in a 120℃ oil bath for azeotropic dehydration for 5 hours. After azeotroping, rotary evaporate the sample to remove residual toluene and seal it for storage. The water content of the sample before dehydration was 0.685%, and the water content after dehydration was 0.05%. Add 40g of dehydrated L-lactide and 160g of dehydrated polyethylene glycol monomethyl ether (sample same as in Example 8) to a three-necked flask. Under stirring at 200rpm, purge the reaction system with nitrogen or argon gas for 30min, then heat the oil bath to 120℃ to melt it. Add 0.6... Stannous octoate was reacted at 120℃ for 10 hours. After the reaction was completed, the reaction system was cooled to room temperature, and 200 ml of dichloromethane was added to dissolve the reaction product. 3 g of high-purity mercapto-modified silica gel was added to the product solution and stirred for 2 hours. The mixture was filtered through a 0.45 μm filter membrane, the filtrate was collected, and most of the solvent was removed by vacuum concentration. Then, 5000 ml of isopropyl ether was slowly added to the concentrate. After the addition was completed, stirring was continued for 0.5 hours, and a solid precipitated. The solid was filtered through filter paper, the filter cake was collected, washed with isopropyl ether, and then dried under vacuum at 30–50℃ to obtain 187 g of mPEG-PLLA copolymer.

[0102] Using the method of this invention, the molecular weight of the prepared mPEG-PLLA copolymer was determined to be Mw 13990 Da, Mn 12835 Da, and Mw / Mn = 1.09. No tin residue was detected. L-lactide residue was 0.26%.

[0103] Examples 10-13 Preparation of the mPEG-PLLA formulation of the present invention

[0104] The preparation methods of mPEG-PLLA in Examples 10-13 are the same as in Example 9, except that the amounts of polyethylene glycol monomethyl ether and lactide used are different.

[0105] Weigh 15g of each of the mPEG-PLLA formulations from Examples 9-13, add them to ultrapure water and stir. Transfer the solution to a 100ml volumetric flask and dilute to the mark with ultrapure water. Filter the diluted solution through a 0.45μm filter membrane and observe the appearance of each formulation. The results are shown in Table 1. See Table 1 for details.

[0106] Table 1

[0107]

[0108] Examples 14-15: In vitro degradation experiments of mPEG-PLLA of the present invention

[0109] In the preparation methods of mPEG-PLLA in Examples 14-15, the experimental conditions are the same as in Example 9, except that the molecular weight of the polyethylene glycol monomethyl ether used is different.

[0110] The polyethylene glycol monomethyl ether polylactic acid copolymers obtained in Examples 9 and 14-15 were prepared into micelle solutions according to the methods in Examples 10-13. After sealing, they were placed in a constant temperature drying oven at 37°C. Samples were periodically removed and freeze-dried, and the changes in molecular weight were detected using the method of this invention. The tests were conducted for a total of 12 weeks. The results are shown in Table 2 below.

[0111] Table 2

[0112]

[0113] While the embodiments disclosed in this invention are as described above, the content is merely for the purpose of facilitating understanding of the invention and is not intended to limit the invention. Any person skilled in the art may make any modifications and changes to the form and details of the implementation without departing from the spirit and scope disclosed herein; however, the scope of patent protection of this invention shall still be determined by the scope defined in the appended claims.

Claims

1. A method for preparing a polyethylene glycol derivative polylactic acid copolymer, comprising the following steps: (1) The polyethylene glycol derivative and lactide are weighed in a ratio of 4-10:1, and under stirring, they are mixed uniformly. The reactants are melted at 80-150°C under vacuum and inert gas protection, and then 0.1-1% tin catalyst is added. The polymerization reaction is completed at 80-150°C to obtain the polyethylene glycol derivative polylactic acid copolymer, wherein, The polyethylene glycol derivative is polyethylene glycol monomethyl ether, the lactide is selected from any one or a combination of L-lactide, D-lactide, and DL-lactide, the inert gas is selected from any one or a combination of nitrogen, argon, and helium, and the tin catalyst is selected from any one or a combination of stannous octoate, stannous chloride, stannous sulfate, dibutyltin diacetate, dibutyltin dibenzoate, tri-n-butylmethoxytin, and dibutyltin dilaurate. (2) After the reaction is completed, the reaction system is cooled to 20℃-35℃, and a good solvent is added to the obtained polyethylene glycol derivative polylactic acid copolymer. The mixture is stirred until completely dissolved to obtain a copolymer solution. Tin is then removed by any one or a combination of modified silica gel column chromatography and modified silica gel adsorption to obtain a tin-removed solution. The good solvent is selected from any one or a combination of tetrahydrofuran, 1,4-dioxane, dichloromethane, chloroform, N,N-dimethylformamide, dimethyl sulfoxide, ethylene glycol diethyl ether, ethylene glycol dimethyl ether, toluene, and p-xylene. The modified silica gel in the modified silica gel column chromatography or modified silica gel adsorption method is mercapto-modified silica gel. (3) Filter the tin removal solution, concentrate it under reduced pressure until the good solvent evaporates, add the unsuitable solvent of polyethylene glycol derivative polylactic acid copolymer to the concentrate, precipitate the solid, filter, wash the filter cake, and dry to obtain polyethylene glycol derivative polylactic acid copolymer, wherein the unsuitable solvent is selected from any one or combination of methanol, ethanol, isopropanol, n-propanol, butanol, acetone, butanone, ethyl acetate, diethyl ether, and isopropyl ether, and the obtained polyethylene glycol derivative polylactic acid copolymer has a molecular weight distribution of 1.01-1.5 and tin residue <10ppm.

2. The method of claim 1, wherein: The polyethylene glycol monomethyl ether is selected from any one or a combination of mPEG-400, mPEG-1000, mPEG-2000, mPEG-4000, mPEG-5000, mPEG-8000 and mPEG-10000.

3. The method of claim 1, wherein: Dehydration of polyethylene glycol derivatives and / or lactide; The water removal method is selected from any one or a combination of azeotropic solvent dehydration and vacuum dehydration.

4. The preparation method according to claim 3, characterized in that: The azeotropic solvent is selected from any one or a combination of benzene, toluene, xylene, and dioxane.

5. The preparation method according to claim 1, characterized in that: The polymerization reaction is completed at 100℃-140℃.

6. The preparation method according to claim 5, characterized in that: The polymerization reaction was completed at 110℃-135℃.

7. The preparation method according to claim 1, characterized in that: The polymerization reaction takes 5-15 hours to complete.

8. The preparation method according to claim 7, characterized in that: The polymerization reaction takes 8-12 hours to complete.

9. The preparation method according to claim 1, characterized in that: Add 0.2%-0.5% tin catalyst.

10. The preparation method according to claim 1, characterized in that: The preparation method satisfies at least one of the following conditions: The amount of silica gel used in the modified silica gel adsorption method is 0.5%-2% of the mass percentage of the copolymer to be purified; The weight-average molecular weight of the prepared polyethylene glycol derivative polylactic acid copolymer is 2000 Da-25000 Da; The molecular weight distribution of the prepared polyethylene glycol derivative polylactic acid copolymer is 1.02-1.25; The tin residue of the prepared polyethylene glycol derivative polylactic acid copolymer is <9 ppm.

11. The preparation method according to claim 10, characterized in that: The preparation method satisfies at least one of the following conditions: The amount of silica gel used in the modified silica gel adsorption method is 1%-1.5% of the mass percentage of the copolymer to be purified; The weight-average molecular weight of the prepared polyethylene glycol derivative polylactic acid copolymer is 4000 Da-22000 Da; The prepared polyethylene glycol derivative polylactic acid copolymer has a weight-average molecular weight of 10,000 Da-13,000 Da.

12. A method for preparing an aqueous solution of a polyethylene glycol derivative polylactic acid copolymer, characterized in that, The preparation method includes: adding the polyethylene glycol derivative polylactic acid copolymer obtained by the preparation method according to any one of claims 1-11 to water and stirring until completely dissolved; transferring the solution to a volumetric flask and making up to volume with water; filtering the solution after making up to volume with a filter membrane, wherein the pore size of the filter membrane is selected from any one of 1 μm, 0.45 μm, and 0.22 μm.

13. The method for preparing an aqueous solution of the polyethylene glycol derivative polylactic acid copolymer as described in claim 12, characterized in that, The water is selected from any one or a combination of ultrapure water, distilled water, and deionized water.

14. The use of the copolymer prepared by the preparation method according to any one of claims 1-11 in the preparation of a carrier for a hydrophobic drug.

15. The use of the copolymer prepared by the preparation method according to any one of claims 1-11 in the preparation of medical and cosmetic products.

16. The use of the polyethylene glycol derivative polylactic acid copolymer prepared by the preparation method according to any one of claims 1-11 in the preparation of a biodegradable injection filler.

17. The application as described in claim 16, characterized in that, The injection site for the filler is selected from any one or a combination of the face, neck, abdomen, chest, buttocks, thigh, calf, upper arm, and lower arm.

18. A composition, characterized in that, The composition comprises a polyethylene glycol derivative polylactic acid copolymer obtained by the preparation method according to any one of claims 1-11.

19. The composition of claim 18, characterized in that, The composition satisfies at least one of the following conditions: The copolymer in the composition has a molecular weight of 7000 Da-15000 Da; The composition further comprises any one or a combination of polyols, amino acids, polypeptides, proteins, nucleic acids, vitamins, polysaccharides, and local anesthetics. The composition further comprises any one or a combination of polyvinyl alcohol, gelatin, gum arabic, guar gum, chondroitin sulfate, hyaluronic acid, sodium carboxymethyl cellulose, polyvinylpyrrolidone, methylcellulose, hydroxypropyl methylcellulose, starch, pectic acid, heparin, glucose, β-cyclodextrin, chitosan, and sodium alginate. The composition is prepared as a liquid injection or a powder injection.

20. The composition of claim 19, characterized in that, The composition satisfies at least one of the following conditions: The copolymer in the composition has a molecular weight of 9000 Da-14000 Da; The copolymer in the composition has a molecular weight of 12000 Da-14000 Da; The liquid injection is selected from any one of hydrogel, suspension, and solution; The powder for injection is a lyophilized powder for injection, which contains any one or a combination of suspension stabilizers, surfactants, and buffers.

21. The composition according to claim 20, characterized in that, The composition satisfies at least one of the following conditions: the suspension stabilizer is selected from any one or a combination of sucrose, maltose, lactose, fructose, dextran, mannitol, trehalose, sorbitol, xylitol, maltitol, oligosaccharide alcohols, and polyethylene glycol; The surfactant is selected from any one or a combination of stearic acid, sodium dodecyl sulfonate, lecithin, alkyl glucoside, polysorbate, sorbitan fatty acid ester, and poloxamer. The buffer is selected from any one or a combination of phosphate-phosphate, citric acid-citrate, EDTA-EDTA salt, citric acid-citrate.

22. A method of combined administration of the composition according to any one of claims 18-21, characterized in that, The composition may be used in combination with any one or a combination of other types of injectable fillers, anesthetics, anti-inflammatory agents, anti-allergens, or other similar agents.

23. The method of combined drug administration as described in claim 22, characterized in that, The combined drug administration method meets at least one of the following conditions: The other types of injectable fillers are selected from any one or a combination of collagen, hyaluronic acid, polymethyl methacrylate, polyacrylamide, silicone, and autologous fat; The anesthetic agent is selected from any one or a combination of lidocaine, procaine, tetracaine, bupivacaine, ropivacaine, diclofenac, morphine, hydrocodone, oxycodone, codeine, fentanyl, sodium pentobarbital, sodium phenobarbital, sodium thiopental, chloralose, ethyl carbamate, and chloral hydrate. The anti-inflammatory agent is selected from any one or a combination of steroidal anti-inflammatory agents and non-steroidal anti-inflammatory agents; The steroidal anti-inflammatory agent is selected from any one or a combination of fluocinolone acetonide, hydrocortisone, and betamethasone. The nonsteroidal anti-inflammatory agents are selected from any one or a combination of aspirin, magnesium salicylate, sodium salicylate, magnesium choline salicylate, diflunisal, disalicylate, ibuprofen, indomethacin, flurbiprofen, phenoxyibuprofen, naproxen, nabumetone, piroxicam, phenylbutazone, diclofenac sodium, fenprofen, ketoprofen, ketoroxyprofen, tetraclofenamic acid, sulindac, and tometidine; the anti-allergic agents are selected from any one or a combination of diphenhydramine, promethazine, chlorpheniramine, sodium cromoglycate, ketotifen, betahistine, montelukast, zafirust, salbutamol, calcium gluconate, and glucocorticoids.

Citation Information

Patent Citations

  • Purification method of polyethylene glycol monomethyl ether-polylactic acid amphiphilic segmented copolymer for injection

    CN105315444A

  • Method for preparing biomedical polyether / polyester block copolymer

    CN102181048A

  • Block copolymer mPEG-b-PLA preparation method

    CN110358063A